Determinasi Kandungan Kadmium (Cd) Di Perairan Pantai Malalayang Sekitar Rumah Sakit Prof Kandou Manado - Mamoribo, Hulda; Rompas, Robert J; Kalesaran, Ockstan J (Universitas Sam Ratulangi, 2015)
This research was conducted by purposive random sampling method with 3 points. Data were analyzed descriptively by comparing the environmental quality standard based on the Ministry of Environment No. 51. 2004. Results of laboratory analysis was the content of Cadmium (Cd) was still below the allowable threshold. Compared to Cd content of fresh water which was 0.0002 mg/L, the Cd content found in this research was lower that was 0.0001 mg/ L. Â Keywords: Kadmium (Cd), Logam berat, Baku Mutu, Pantai Malalayang, RS Prof Kandou.